Association of Vitamin D with Diabetic Neuropathy among Sudanese Patients with Type 2 Diabetes Mellitus - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Neuropathy is a common diabetic microvascular complication which reduces quality of life; causing pain and irritation in lower limbs and may result in amputation. Several Studies documented that vitamin D deficiency have extra skeletal effects including poor glycemic control and microvascular complications.Objectives:To explore the relationship between levels of vitamin D and diabetic neuropathy in Sudanese patients with type 2 diabetes mellitus.Methods:In this cross-sectional case control and hospital based study conducted at Jabber Abu Eliz Diabetes Centre (JAEDC), from February 2015 to November 2018, Sixty diabetic patients (thirty patients with neuropathy and thirty patients without neuropathy), and sixty healthy subjects were compared in terms of levels of vitamin D, C-peptide, lipid profile, HbA1C, C-reactive protein, and MAU. SPSS software was used for analysis of clinical variables.Results:Vitamin D levels where significantly decreased in diabetic patients and also in those with neuropathy when compared to those without neuropathy (P < 0.05) Vitamin D correlated significantly with age P (0.016), insignificantly with disease duration, BMI, HbA1C and MAU (P > 0.05). 86.8% of patients with neuropathy had vitamin D deficiency and 6.6% had insufficiency. Vitamin D levels where significantly reduced with increasing severity of neuropathy (P 0.001).Conclusion:Vitamin D levels are significantly decreased in diabetic patients especially in those with neuropathy. Severity of neuropathy is significantly correlated to severity of vitamin D deficiency. Diabetic patients should be screened for vitamin D level and supplementation should be prescribed to correct the deficiency.